Implementasi Strategi Pemasaran dalam Meningkatkan Kepuasan Konsumen - Dhana, Dyno Senja Rama; Latifah, Umi; Mastura, Zanuba Ana (Aktualisasi Pengabdian Masyarakat, 2023)
Marketing is part of business management and is one of the most important because marketing will directly affect the smooth running and success of a business in achieving its goals. It is important for traders to know the right and correct trading methods for the products to be sold in the market. The marketing strategy used is to set prices according to the pockets of the community. One way to do this in developing this business is to prioritize customer service. If the increase in human resources is going well, consumers are also one of the important areas that you should pay attention to. When viewed from the advantages of the marketing strategy of its products, namely being able to put forward its own taste and differentiation so as to be able to provide the right product in the scope of the general public. The advantages of the marketing strategy for Umkm Batagor Qhuinsa are using products that maintain taste and hygienic processes. In addition, it has prices that are right in the pockets of the community and strategic distribution locations and easy to reach. The drawbacks of the marketing strategy carried out by the batagor qhuinsa umkm are the lack of promotion and strict competitiveness.